Respostas
respondido por:
1
X elevado a 2 + 12x - 12= 1
X elevado a 2 + 12x - 12 -1 =0
X elevado a 2 + 12x - 13 =0
Formula
/\= 12 ao quadrado -4 . 1 . (-13)
/\= 144 + 53
/\= 196
X= - 12 + ou - a raiz quadrada de 196
X= -12 + ou - 14
X= -12 + 14 = 2/2 = 1
X= -12 - 14 = -26/2 = -13
Resposta final = 1
X elevado a 2 + 12x - 12 -1 =0
X elevado a 2 + 12x - 13 =0
Formula
/\= 12 ao quadrado -4 . 1 . (-13)
/\= 144 + 53
/\= 196
X= - 12 + ou - a raiz quadrada de 196
X= -12 + ou - 14
X= -12 + 14 = 2/2 = 1
X= -12 - 14 = -26/2 = -13
Resposta final = 1
alcides182:
Mas Aonde Está a Resposta??
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás